Kecerdasan Majemuk dan Karakter Mahasiswa Fakultas Ilmu Pendidikan: Analisis Berdasarkan Tes Multiple Intelligences Score (MIS) - Anggelina Theresia Pandiangan; Dian Rumahorbo; Elvelina Dwi Glorya Sianturi; Nurhasanah Daulay; Selfi Olivia Siregar; Stephanie Alta Gracia Siregar (CV. Eracita Grup, 2025)
This study aims to describe the profile of multiple intelligences and student character in the Faculty of Education at Universitas Negeri Medan based on the Multiple Intelligences Score (MIS). The research employed a descriptive quantitative approach using a survey method involving 25 female students from four study programs: Primary School Teacher Education, Early Childhood Teacher Education, Guidance and Counseling, and Community Education. Data were collected through the MIS test based on Howard Gardner’s theory of multiple intelligences and a character questionnaire referring to Thomas Lickona’s character education framework. The data were analyzed using descriptive statistics in the form of mean scores and percentages. The results indicate that naturalistic intelligence obtained the highest average score, while intrapersonal intelligence showed the lowest score. In terms of character, resilience emerged as the most prominent trait, whereas independence and initiative demonstrated relatively lower scores. The study concludes that students possess diverse multiple intelligences and generally positive character traits; however, balanced learning strategies integrating the development of multiple intelligences and character are still required.